The Role of Customer Satisfaction in Linking Service Quality and Customer Loyalty in E-Logistics Management in West Java - Nurul Aziz Pratiwi; Ratih Hurriyati; Puspo Dewi Dirgantari (Penerbit Jurnal Indonesia, 2025)
The rapid growth of e-commerce in Indonesia has increased the strategic role of e-logistics services in shaping customer experience and competitiveness, particularly in West Java as one of the largest logistics markets. This study aims to examine the effect of e-logistics service quality on customer loyalty, with customer satisfaction as a mediating variable. A quantitative research approach was employed using a survey method. Data were collected from 200 e-logistics service users in West Java through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results reveal that e-logistics service quality has a positive and significant effect on customer satisfaction. Customer satisfaction also has a positive and significant effect on customer loyalty. However, e-logistics service quality does not directly influence customer loyalty. Further analysis confirms that customer satisfaction fully mediates the relationship between e-logistics service quality and customer loyalty. These findings indicate that improving service quality alone is insufficient to foster customer loyalty unless it is translated into perceived satisfaction. This study highlights the strategic role of customer satisfaction as a key mechanism linking service quality and loyalty in the e-logistics context. The results provide theoretical contributions to service quality and loyalty models in digital logistics, as well as practical implications for e-logistics providers and e-commerce platforms in designing customer-oriented service strategies to enhance long-term customer retention in West Java.